2003
DOI: 10.1002/app.12611
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the weak link of wool fibers

Abstract: ABSTRACT:The variance of fiber morphology along a fiber and the natural and artificial flaws in the fiber structure represent the primary reasons for the weak link of fibers. Accordingly, the fiber weak link can be divided into two types, that is, the geometrical thinnest part and the structural weak point. Scanning electron microscopic observation was used to characterize the morphological features of the fiber weak points whose forms are the normal thin sections, natural flaws, and artificial damage. Both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…The distribution of weak-links can be random or specific. [72,73] Case 6 (Recombination or cross-linking during scission): A wealth of experimental study showed that most cases of auto-oxidation or radical-induced reactions, molecular fraction breakdown (b) is accompanied by recombination, crosslinking or bimolecular association (a). [74][75][76][77] Such a situation favours the recombination of different sized broken fragments with parent chains originating from HMW, MMW or LMW domains at a reactive site (e.g., unsaturated bonds in the backbone or weaker links in the side chain) for chain propagation.…”
Section: Simulated Mwd During Decaymentioning
confidence: 99%
“…The distribution of weak-links can be random or specific. [72,73] Case 6 (Recombination or cross-linking during scission): A wealth of experimental study showed that most cases of auto-oxidation or radical-induced reactions, molecular fraction breakdown (b) is accompanied by recombination, crosslinking or bimolecular association (a). [74][75][76][77] Such a situation favours the recombination of different sized broken fragments with parent chains originating from HMW, MMW or LMW domains at a reactive site (e.g., unsaturated bonds in the backbone or weaker links in the side chain) for chain propagation.…”
Section: Simulated Mwd During Decaymentioning
confidence: 99%
“…Besides, we have also assumed that the geometrical thinnest part is the fiber weak link. However, Yu et al [25] found for wool that the probability of fiber breakage at minimum diameter was in the range of 40 -52% as the natural and artificial flaws in the fiber structure represent the primary reasons for the weak link of fibers. On the other hand, flax fibers are susceptible to damage in compression through the formation of kink bands [9,26].…”
Section: Single Fiber Tensile Test Measurementsmentioning
confidence: 99%
“…To study the oil sorption behavior of super oil‐absorbent composites, the dried samples (0.1 g) in a stainless steel mesh were immersed in mixture of oil (5 mL) and distilled water (15 mL) at different temperature (313.15 K, 323.15 K, and 333.15 K) to reach sorption equilibrium . The resultant swollen samples then were drained and weighed to discuss thermodynamic parameters including free energy Δ G , enthalpy Δ H, and entropy Δ S according to the following formulas : ΔG=RTlnKd lnKd=ΔS/RΔH/RT …”
Section: Methodsmentioning
confidence: 99%
“…In order to achieve above-mentioned objectives, the environmental-friendly and renewable natural oil-absorption materials, such as poplar [16], cotton [17], wool fibers [18], kapok fiber [19], and sea buckthorn branches [20] have been proposed currently to partially combine the conventional petroleum-based polymers for purpose of construction of composite super oil-absorbent materials. Widely adopted monomers, including methyl-meth-acrylate and butyl-acrylate, have been successfully grafted onto the surface of natural oilabsorbent of plant fibers [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%